Corporate Action : Pengaruh Stock Repurchase dan Kepemilikan Keluarga terhadap Audit Fee - Windi Marlianita Fitri; R Nelly Nur Apandi (Universitas Winaya Mukti, 2019)
This study aims to examine the effect of stock repurchase on audit costs with family ownership as a moderating variable in non-financial companies listed on the Indonesia Stock Exchange (BEI) in 2014—2016. Audit fees in this study were measured by looking at the total audit fees listed in the company's annual report. The research method used is to use quantitative descriptive methods. The population in the study was 110 non-financial companies listed on the Indonesia Stock Exchange (IDX) in 2014—2016. The sample was chosen based on a purposive sampling technique with several criteria. The data analysis technique used in the study is multiple regression models. The results of hypothesis testing in the study indicated that stock repurchase had a positive effect on audit fees and family ownership was considered capable of weakening the influence of stock repurchase on audit fees.